Distal end of the atrioventricular nodal artery predicts the risk of atrioventricular block during slow pathway catheter ablation of atrioventricular nodal re-entrant tachycardia. Issue 5 (1st May 2000) - Lin, J-L; Huang, S K S; Lai, L-P; Lin, L-J; Chen, J-H; Tseng, Y-Z; Lien, W-P
Abstract : OBJECTIVE: To search for a reliable anatomical landmark within Koch's triangle to predict the risk of atrioventricular (AV) block during radiofrequency slow pathway catheter ablation of AV nodal re-entrant tachycardia (AVNRT). PATIENTS AND METHODS: To test the hypothesis that the distal end of the AV nodal artery represents the anatomical location of the AV node, and thus could be a useful landmark for predicting the risk of AV block, 128 consecutive patients with AVNRT receiving slow pathway catheter ablation were prospectively studied in two phases. In phase I (77 patients), angiographic demonstration of the AV nodal artery and its ending was performed at the end of the ablation procedure, whereas in the subsequent phase II study (51 patients), the angiography was performed immediately before catheter ablation to assess the value of identifying this new landmark in reducing the risk of AV block. Multiple electrophysiologic and anatomical parameters were analysed. The former included the atrial activation sequence between the His bundle recording site (HBE) and the coronary sinus orifice or the catheter ablation site, either during AVNRT or during sinus rhythm. The latter included the spatial distances between the distal end of the AV nodal artery and the HBE and the final catheter ablation site, and the distance between the HBE and the tricuspid border at the coronary sinus orifice floor. RESULTS: In phase I, nine of the 77 patients had complications of transient (seven patients) or permanent (two patients) complete AV block during stepwise, anatomy guided slow pathway catheter ablation. These nine patients had a wider distance between the HBE and the distal end of the AV nodal artery, and a closer approximation of the catheter ablation site to the distal end of the AV nodal artery, which independently predicted the risk of AV block. In contrast, none of the available electrophysiologic parameters were shown to be reliable. When the distance between the distal end of the AV nodal artery and the ablation target site was more than 2 mm, the complication of AV block virtually never occurred. In phase II, all 51 patients had successful elimination of the slow pathways without complication when the ablation procedure was guided by preceding angiography with identification of the distal end of the AV nodal artery. CONCLUSIONS: The distal end of the AV nodal artery shown by angiography serves as a useful landmark for the prediction of the risk of AV block during slow pathway catheter ablation of AVNRT.